PECULIARITIES OF SHEAR STRENGTH OF CLAYEY SOILS IN CONDITIONS OF VIBRODYNAMIC IMPACTS IN THE WIDE RANGE OF CONSISTENCY: (with the purpose to assess slope stability) (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
In the article the results of laboratory studies of clayey rock samples of three different consistencies and humidities are discussed for the purpose of revealing the distinctive features of shear strength values under the different conditions, i.e. under the cyclic shearing stresses. It is experimentally substantiated that appropriate adjusting of the accepted design schemes for a real assessment of slope stability is a problem that requires a prompt solution.
Keywords: clayey soils; torsional vibration impact; shear stresses